KESIAPAN MAHASISWA MENJADI GURU GEOGRAFI PADA JURUSAN GEOGRAFI FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI PADANG - Purdianingrum, Vika; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The purpose of this study was to determine how much students are prepared to become geography teachers in the geography department of the 2017 education study program, Faculty of Social Sciences, Padang State University.This type of research uses descriptive quantitative. The population in this study was the 2017 class of education geography students, totaling 137 students. Sampling of respondents used the Slovin formula, with an error rate of 5% from 137 so that 102 students were sampled. The sampling technique of this study used proportional random sampling. Data collection techniques using a questionnaire. The data analysis technique used was descriptive analysis.The results of this study found that the readiness to become a geography teacher for students majoring in geography in the 2017 class of education study program was obtained an average of 3.94 and was in the very ready category. So that there are no doubts and worries by researchers, because in this study it proves that students majoring in geography in the 2017 class of education study programs are ready to become geography teachers.